KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS IV PADA MODEL KOOPERATIF TIPE JIGSAW BERBANTUAN MEDIA ENGKLEK MATEMATIKA - Elsa Noviyanti; Sastra Wijaya; Fauzi Fadliansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of learning mathematics is not just to achieve student learning outcomes, but rather to achieve basic mathematical skills, namely communication. Based on the results of an interview with the class teacher with the initials "NH" it is known that "students' mathematical communication skills are not yet optimal." This statement is reinforced by the results of the initial mathematical communication ability test, there are 26 out of 36 students who cannot use mathematical notation or symbols and operations correctly, does not show what is known and what is asked in the question, and has not shown the ability to express reasons or bases in explaining problem solving strategies well. This type of Quasi experimental design research aims to determine the effect of the Jigsaw type cooperative learning model assisted by mathematical hopscotch media on mathematical communication skills. All class IV students at SDN Cibeber III as a population. Sampling used a purposive sampling technique based on the Slovin formula as the specified sample size. The findings show that the mathematical communication skills of students who used the Jigsaw type cooperative model assisted by mathematical hopscotch media in the experimental class showed an average score of 76.53 while in the control class showed an average score of 60.00. The results of the hypothesis test show that there is an influence of the use of the Jigsaw type cooperative learning model assisted by mathematical hopscotch media on the mathematical communication skills of class IV students at SDN Cibeber III Cilegon